Brill's companion to the reception of Herodotus in antiquity and beyond - Priestley, Jessica; Zali, Vasiliki (Brill's companions to classical reception, 2016)
Preliminary Material -- Introduction /Jessica Priestley and Vasiliki Zali -- 1 Herodotus in Thucydides: A Hypothesis /Marek Wecowski -- 2 Herodotus and His Successors: The Rhetoric of the Persian Wars in Thucydides and Xenophon /Vasiliki Zali -- 3 Duris of Samos and a Herodotean Model for Writing History /Christopher A. Baron -- 4 “This is What Herodotus Relates”: The Presence of Herodotus’ Histories in Josephus’ Writings /Eran Almagor -- 5 History without Malice: Plutarch Rewrites the Battle of Plataea /John Marincola -- 6 Herodotus in Renaissance France /Benjamin Earley -- 7 The Anti-Thucydides: Herodotus and the Development of Modern Historiography /Neville Morley -- 8 Herodotus’ Reception in Ancient Greek Lexicography and Grammar: From the Hellenistic to the Imperial Age /Olga Tribulato -- 9 Herodotus’ Reputation in Latin Literature from Cicero to the 12th Century /Félix Racine -- 10 Valla’s Herodotean Labours: Towards a New View of Herodotus in the Italian Renaissance /Adam Foley -- 11 Herodotus and Narrative Art in Renaissance Ferrara: The Translation of Matteo Maria Boiardo /Dennis Looney -- 12 The ‘Rediscovery’ of Egypt: Herodotus and His Account of Egypt in the Voyage dans la Basse et la Haute-Égypte (1802) by Vivant Denon /Andreas Schwab -- 13 Not beyond Herodotus? Psammetichus’ Experiment and Modern Thought about Language /Benjamin Eldon Stevens -- 14 Herodotus (and Ctesias) Re-enacted: Leadership in Xenophon’s Cyropaedia /Vivienne Gray -- 15 Pausanias and the Footsteps of Herodotus /Greta Hawes -- 16 Ryszard Kapuściński’s Travels with Herodotus: Reportage from the Self /Kinga Kosmala -- 17 Herodotus in Fiction: Gore Vidal’s Creation /Heather Neilson -- Bibliography -- Index.
Keywords: Herodotus -- History; Herodotus -- Appreciation; Konferenzschrift -- 2013 -- Bristol; Rezeption; Herodotus